К устойчивости тривиального решения неавтономной квазилинейной системы в случае кратных корней характеристического уравнения - Витриченко, И.Е. (Український математичний журнал, 1994)
For t↑ω, ω ≤ +∞, we obtain sufficient conditions for Lyapunov stability of the zero solution of a specific nonautonomous quasilinear differential system in the case where the matrix of the first-degree approximation has the Jordan form with triangular blocks. Methods to reduce certain classes of general differential systems to differential systems of special type are given.